Adaptive processes of Staphylococcus aureus isolates during the progression from acute to chronic bone and joint infections in patients. (1st April 2016) - Trouillet‐Assant, Sophie; Lelièvre, Lucie; Martins‐Simões, Patrícia; Gonzaga, Luiz; Tasse, Jason; Valour, Florent; Rasigade, Jean‐Philippe; Vandenesch, François; Muniz Guedes, Rafael Lucas; Ribeiro de Vasconcelos, Ana Tereza; Caillon, Jocelyne; Lustig, Sebastien; et al.
Summary: Staphylococcus aureus bone and joint infection (BJI) is associated with significant rates of chronicity and relapse. In this study, we investigated how S. aureus is able to adapt to the human environment by comparing isolates from single patients with persisting or relapsing BJIs that were recovered during the initial and recurrent BJI episodes. In vitro and in vivo assays and whole‐genome sequencing analyses revealed that the recurrent isolates induced a reduced inflammatory response, formed more biofilms, persisted longer in the intracellular compartments of host bone cells, were less cytotoxic and induced less mortality in a mouse infection model compared with the initial isolates despite the lack of significant changes at the genomic level. These findings suggest that S. aureus BJI chronicization is associated with an in vivo bacterial phenotypical adaptation that leads to decreased virulence and host immune escape, which is linked to increased intraosteoblastic persistence and biofilm formation.